The used of aqueous urea solution in reduction of noxious emissions in bio fuel combustion system using selective non-catalytic reduction - Mohamad Shaiful Ashrul, Ishak; Mohammad Nazri, Mohd. Jaafar (Canadian Center of Science and Education (CCSE), 2011)
Link to publisher's homepage http://ccsenet.org/